2015
DOI: 10.1371/journal.pone.0139406
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping by Sequencing for SNP-Based Linkage Map Construction and QTL Analysis of Chilling Requirement and Bloom Date in Peach [Prunus persica (L.) Batsch]

Abstract: Low-cost, high throughput genotyping methods are crucial to marker discovery and marker-assisted breeding efforts, but have not been available for many ‘specialty crops’ such as fruit and nut trees. Here we apply the Genotyping-By-Sequencing (GBS) method developed for cereals to the discovery of single nucleotide polymorphisms (SNPs) in a peach F2 mapping population. Peach is a genetic and genomic model within the Rosaceae and will provide a template for the use of this method with other members of this family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
98
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 31 publications
11
98
0
Order By: Relevance
“…These methods involve next-generation sequencing near restriction sites in genome sequences and are collectively described as reduced representation library sequencing (Davey et al, 2011;Jiang et al, 2016). SNP-based linkage map construction and QTL analysis using GBS have been carried out in several plant species (Bielenberg et al, 2015). The genotyping-by-sequencing method (GBS; Sonah et al, 2013) is a simple library preparation method that can be used along with restriction site-associated DNA sequencing (Baird et al, 2008).…”
mentioning
confidence: 99%
“…These methods involve next-generation sequencing near restriction sites in genome sequences and are collectively described as reduced representation library sequencing (Davey et al, 2011;Jiang et al, 2016). SNP-based linkage map construction and QTL analysis using GBS have been carried out in several plant species (Bielenberg et al, 2015). The genotyping-by-sequencing method (GBS; Sonah et al, 2013) is a simple library preparation method that can be used along with restriction site-associated DNA sequencing (Baird et al, 2008).…”
mentioning
confidence: 99%
“…Additionally, GBS has been shown to be a valid tool for genomic diversity studies (Fu and Peterson, 2011). Recently this approach was reported for quantitative trait loci (QTL) analyses in peach and other species (Ward et al, 2013; Bielenberg et al, 2015). Several microarrays using the Infinium R platform for SNP genotyping are available in different Rosaceae species such as peach, apple, and cherry (Chagné et al, 2012; Verde et al, 2012).…”
Section: Next Generation Sequencingmentioning
confidence: 99%
“…Similarly to fruit quality, high-throughput sequencing helped to dissect complex traits and to identify candidate genes for other traits such as adaptability to chilling (Bielenberg et al, 2015), and resistance to brown rot (Martínez-García et al, 2013), bacterial spot (Yang et al, 2013), and PPV (Zuriaga et al, 2013). …”
Section: Impact Of Ngs On Breedingmentioning
confidence: 99%
“…The QTLs for apricot blooming initiation time were located on LG1 and LG4 (Dirlewanger et al, ; Olukolu et al, ; Socquet‐Juglard et al, ). In peach, major QTLs for chilling requirements and blooming time were detected on LG1, LG4, and LG7 (Bielenberg et al, ; Fan et al, ; Zhebentyayeva et al, ). Genome‐wide association studies for CR in peach identified seven association peaks, located on LG 1, 3, 7, and 8.…”
Section: Introductionmentioning
confidence: 99%